Apparatus Competence, Internal Control System, Information Technology Utilization and Accountability of Village Fund Allocation Management - Mukarramah, Nurtisatul (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This research aims to determine and analyze the influence of apparatus competency, internal control systems, and information technology on village government accountability in managing village fund allocations. Research Design and Methodology: The data analysis method to be employed consists of descriptive statistical analysis, validity and reliability testing, classical assumption verification, and hypothesis testing through multiple linear regression analysis, t-tests, and F-tests. Findings and Discussion: The research results show that apparatus competency has a negative and insignificant effect on village government accountability in managing village fund allocation. Meanwhile, the internal control system and information technology have a positive and significant impact on village government accountability in managing village fund allocations. Implications: The practical impact of the research results is the need for serious attention to increasing competence, implementing an effective internal control system, and optimizing the use of information technology in managing village funds.